PHYSICAL EDUCATION PRE-SERVICE TEACHERS: HEALTH-AND ACTIVE LIFE STYLE APTITUDE (Fiep Bulletin - online, 2013)
The World Health Organization (WHO) challenged active life style for non communicable diseases (NCDs).The Physical inactivity is one of risk factor for global mortality (6% of deaths globally).Physical inactivity became the fourth leading risk factor after high blood pressure (13%), tobacco use (9%) and high blood glucose (6%); these factors together with and overweight/obesity are responsible for 5% of NCDs (WHO, 2009).The inactivity levels are increasing in many countries and they can cause onset of the following diseases: cardiovascular disease (30%), diabetes (27%) and cancer (21-25%). To hell overcoming this matter the WHO wrote some important documents: Global strategy for diet and Physical Activity (2004) and Global strategy for Physical Activity (2010-2013) based on Global Recommendations on Physical Activity for Health (GRPAH. It  is  guidelines on “the dose-response relationship between physical activity and health benefits” (WHO, 2010). The health prevention outcomes:cardio respiratory health (coronary heart disease, cardiovascular disease, stroke and hypertension); metabolic health (obesity and diabetes); musculoskeletal health (bone health, osteoporosis); cancer (breast and colon cancer); functional health and prevention of falls and trauma; depression.The aims survey on PA gave scientific evidence for:• health policy (inform national physical activity policies and other public health interventions);• health governance (provide the starting point to the establishment of goals and objectives for physical activity promotion at national level);• health management (foster inter- intersectoral collaboration and contribute to setting up national goals and objectives regarding physical activity promotion);• health empowerment (provide a foundation for physical activity promotion initiatives and participation) ;• health funding (justify the allocation of resources to physical activity promotion interventions);• health networking  (create a framework for joint action for all other relevant stakeholders around the same goal;• health innovation (provide an evidence-based document that enables all relevant stakeholders to transfer policy into action with the allocation of the appropriate resources); • health prevention  (facilitate national surveillance and monitoring mechanisms to monitor population levels of physical activity) .(WHO, 2010)